2018
DOI: 10.1021/acs.chemmater.8b01634
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Study of Sodium Insertion in the λ-Mn2O4 and Dis/Ordered λ-Mn1.5Ni0.5O4 Spinels

Abstract: The main challenge of sodium-ion batteries is cycling stability, which is usually compromised due to strain induced by sodium insertion. Reliable high-voltage cathode materials are needed to compensate the generally lower operating voltages of Na-ion batteries compared to Li-ion ones. Herein, density functional theory (DFT) computations were used to evaluate the thermodynamic, structural, and kinetic properties of the high voltage λ-Mn2O4 and λ-Mn1.5Ni0.5O4 spinel structures as cathode materials for sodium-ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…All configurations have reached a convergence threshold of 0.01 eV Å −1 in force. [ 19 ] It should be noticed that the experimental voltage can be realized only by PBE without U . The usual U value 3.8 or 4.2 eV used in LiMn 2 O 4 calculations can't repeat the experimental average voltage 2.8 V and overestimates the average voltage to 3.5 eV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All configurations have reached a convergence threshold of 0.01 eV Å −1 in force. [ 19 ] It should be noticed that the experimental voltage can be realized only by PBE without U . The usual U value 3.8 or 4.2 eV used in LiMn 2 O 4 calculations can't repeat the experimental average voltage 2.8 V and overestimates the average voltage to 3.5 eV.…”
Section: Methodsmentioning
confidence: 99%
“…The usual U value 3.8 or 4.2 eV used in LiMn 2 O 4 calculations can't repeat the experimental average voltage 2.8 V and overestimates the average voltage to 3.5 eV. [ 19,20 ]…”
Section: Methodsmentioning
confidence: 99%
“…Reproduced with permission. [ 155 ] Copyright 2018, American Chemical Society. d) Cyclic voltammogram (CV) curves of λ ‐MnO 2 electrode at various scan rates in 1 m Na 2 SO 4 solution.…”
Section: Faradaic Electrode Materials For CDImentioning
confidence: 99%
“…Some earlier work showed that the electrochemical sodiation of the λ ‐MnO 2 could generate topological deformations, resulting in a local phase transition from the spinel to O′3 layered structure. On the other hand, more recent studies [ 155–157 ] reported that reversible Na + insertion/extraction could be achieved by initially filling the interstitial 8a tetrahedral sites and 16c octahedral sites of λ ‐MnO 2 as displayed in Figure 7c. The CV curves in 1 m Na 2 SO 4 solution (Figure 7d) show that there are two pairs of oxidation/reduction peaks emerged, which could be ascribed to the insertion/extraction of Na + in the 8a and 16c sites of λ ‐MnO 2 , respectively.…”
Section: Faradaic Electrode Materials For CDImentioning
confidence: 99%
“…The charge/discharge dynamics, the specific role of each constituent element in the material, the electrical conduction properties, and the surface chemistry of these electrodes present several fundamental questions, despite numerous studies carried out so far. Density functional theory (DFT) calculations have proven to be a useful technique for evaluating the thermodynamic, structural, and kinetic properties of manganese oxide (MnO 2 ) with monoclinic [27] and spinel structure [28] for their use as cathode materials for NIBs. Therefore, we applied an advanced quantum mechanics (QM) method based on DFT [29,30] and combined with a statistical approach to evaluate the Na 0.85 Li 0.17 Ni 0.21 Mn 0.64 O 2 (NLNMO) material as P2-type layered oxide with the promising application as a cathode electrode in NIBs [31].…”
Section: Introductionmentioning
confidence: 99%